2007
DOI: 10.1080/15324980701603573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indole Acetic Acid on the Synergistic Interactions ofBradyrhizobiumandGlomus fasciculatumon Growth, Nodulation, and Nitrogen Fixation ofDalbergia sissooRoxb

Abstract: The legume Dalbergia sissoo Roxb is an important forest tree of the arid and semiarid regions. The efficiency of Bradyrhizobium (Ds Rhz-9) and Glomus fasciculatum (Thaxter sensu Gerd.) Gerd. and Trappe to promote growth of D. sissoo and the effect of indole acetic acid (IAA) on the tripartite symbiotic association was studied in a pot experiment. Parameters like plant growth, nodulation, total phosphorus, total nitrogen content, nitrogenase activity of root nodules (acetylene reduction assay), and arbuscular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, two studies found that AM fungal colonization decreased in the presence of rhizobia, but Jia et al (2004) also demonstrated that the photosynthetic rate was higher in plants infected with both symbionts concurrently. Similarly, Niranjan et al (2007) found that while AM fungal colonization decreased with rhizobia, nitrogen fixation was higher in the presence of both symbionts. While many of the interactions were positive, they were not usually synergistic (but see Pacovsky et al 1986;Ferrari and Wall 2008), as plants often did not perform better than expected given symbiont individual effects.…”
Section: Mycorrhizal and Nitrogen-fixing Symbiontsmentioning
confidence: 93%
“…However, two studies found that AM fungal colonization decreased in the presence of rhizobia, but Jia et al (2004) also demonstrated that the photosynthetic rate was higher in plants infected with both symbionts concurrently. Similarly, Niranjan et al (2007) found that while AM fungal colonization decreased with rhizobia, nitrogen fixation was higher in the presence of both symbionts. While many of the interactions were positive, they were not usually synergistic (but see Pacovsky et al 1986;Ferrari and Wall 2008), as plants often did not perform better than expected given symbiont individual effects.…”
Section: Mycorrhizal and Nitrogen-fixing Symbiontsmentioning
confidence: 93%
“…A positive effect of mycorrhization on beneficial plant-microbe interactions has been noted. For example, promotion of the interaction or synergistic effects have been described with regard to plant associations with nitrogen-fixing bacteria (Jia et al, 2004;Niranjan et al, 2007;Ferrari and Wall, 2008;Larimer et al, 2010); phosphatesolubilizing bacteria (Toro et al, 1996;Belimov et al, 1999;Kohler et al, 2007); biocontrol agents (Haggag and Abd-El Latif, 2001;Martínez-Medina et al, 2009;Martínez-Medina et al, 2010;Saldajeno and Hyakumachi, 2011); and plant growth-promoting microorganisms (Meyer and Linderman, 1986;Chandanie et al, 2005Chandanie et al, , 2006Chandanie et al, , 2009.…”
Section: Mycorrhiza Effects On Below-ground Interactionsmentioning
confidence: 96%
“…Moreover, the plant is well suited to grow under extreme conditions like contaminated, degraded and marginal lands. [31][32][33]. The biomass production and carbon sequestration potential of D. sissoo has been analyzed in the Tarai region of Central Himalaya [33].…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggested that five-years aged coppice shoots of the Dalbergia plantation on sodic land produced aboveground biomass of 13.52 Mg ha −1 [26] with the maximum proportion in the stem-wood (9.84 Mg ha −1 ), followed by branch-wood (2.92 Mg ha −1 ) and leaf (0.78 Mg ha −1 ). Furthermore, Singh et al [30] reported luxurious growth of D. sissoo on sodic land in northern India with higher fuelwood properties, including a wood density of 0.73 g cm −3 , and an FVI of 777 [30] Previous studies have also proved that Dalbergia plantations can improve soil properties like nitrogen, phosphorus and potassium content [34], and different methods have been employed to enhance the growth of the plant [31].…”
Section: Introductionmentioning
confidence: 99%